Relationship and communication in music therapy: A response to North (2014). (November 2014) - Watson, Tessa
In this response to North's article and in the interdisciplinary spirit of the conference, three areas are considered: engaging people with severe intellectual disabilities in music therapy, with particular focus on the concepts of containment and attachment; the importance of supporting and developing staff through music therapy work; and the richness of transdisciplinary or joint working. The issues raised highlight the responsibility that music therapists have in sharing the particular ways in which we use the communicative aspects of music with parents, carers, colleagues, and other professional groups and academic communities, and they are a reminder of the communicative power of music.